Fisura labiopalatina bilateral y su abordaje odontológico multidisciplinario. Reporte de caso - Leiva Villagra, Noemí (2017)
The cleft lip and palate is a congenital craniofacial malformation that develops from embryological defects during the formation of the face. The anomalies occur mainly in the upper lip, premaxilla, palate and nasal floor. Here we introduce a case report of a patient who was admitted at 7 years old diagnosed with bilateral cleft lip and palate treated in the Craniofacial Malformations Unit of the Faculty of Dentistry of the University of Chile. The patient presented a Class III skeletal relationship, lack of development of the facial middle third, protruding position of the premaxilla, a bilateral Class III molar malocclusion with malposition and dental crowding. An orthopedic treatment of maxillary expansion was performed followed by an orthodontic treatment with fixed appliance. Following the extraction of supernumerary teeth, bone graft surgery and gingivoperiosteoplasty, she was referred to a rehabilitator who made an adhesive bridge and dental veneers, restoring aesthetics to the anterosuperior sector. Finally, removable upper and lower dental appliances were installed in the patient. Thus, satisfactory results were obtained in terms of a functional, stable and esthetic occlusion.